Three-dimensional observation of TiO2 nanostructures by electron tomography - Suh, Young Joon; Lu, Ning; Park, Seong Yong; Lee, Tae Hun; Lee, Sang Hoon; Cha, Dong Kyu; Lee, Min Gun; Huang, Jie; Kim, Sung-Soo; Sohn, Byeong-Hyeok; Kim, Geung-Ho; Ko, Min Jae; et al. (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
Three-dimensional nanostructures of TiO2 related materials including nanotubes, electron acceptor materials in hybrid polymer solar cells, and working electrodes of dye sensitized solar cells (DSSCs) were visualized by electron tomography as well as TEM micrographs. The regions on the wall of TiO2 nanotubes where the streptavidins were attached were elucidated by electron tomogram analysis. The coverage of TiO2 nanotubes by streptavidin was also investigated. The TiO2 nanostructures in hybrid polymer solar cells made by sol-gel and atomic layer deposition (ALD) methods and the morphologies of pores between TiO2 particles in DSSCs were also observed by reconstructed three-dimensional images made by electron tomography. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: VISUALIZATION; NANOTUBES; MICROSTRUCTURE